IMPLEMENTASI GOOD COORPORATE GOVERNANCE PERBANKAN UNTUK MENCEGAH PRAKTEK MONOPOLI TERHADAP PERUSAHAAN ASURANSI - Yanti Sugiyanti Sendy Ramania (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2015)
BRI has been committed in implementing GCG, but according to the research findings GCG policy has been carried out as stipulated in the law, but it is still found weaknesses in the implementation of GCG in order to have any legal consequences for the implementation of sanctions that administrative sanctions, civil and criminal. Relative to the parties involved in violations of competition and good corporate governance policy that the BRI SK Bandung and Bringin Life must always consider the legal norms in force to prevent violations of monopoly and GCG.